Instalações geográficas e sua aplicabilidade em escolas da rede básica de ensino na região do Cariri – Ceará - Alexandre, Diego Leite (2019)
Defined as a form of representation of a geographic content by signs and symbols applied on materials produced or not by man, the methodology geographic installation dialogues with art, research and creativity enabling the articulation between theory and practice and finding, in classroom practice, a teaching and learning process based on the construction of knowledge. This work, therefore, aims to investigate the applicability of this teaching methodology by teachers Schools in the basic education network of the Cariri region (EC). To meet our goals, enabling our proposal for research, We did a reading and bibliographic selection of some concepts that gave the theoretical-methodological support to our reflections and writing, such as geographic installation, geography teaching, teaching Praxis, signs and symbols, research, creativity and evaluation. In addition to reading and bibliographic selection, we used the participant observation technique through which we performed the follow-up of teachers In the development of the methodology in the classroom, paying attention to its procedural and intervening steps, in some moments, In the constructive process. At the end of the participant observation we conducted a semi-structured interview with the teachers In order to understand their perceptions about this teaching methodology, their contributions to the teaching and learning process, as well as its possibilities and limits regarding the applicability of the methodology. Therefore, it was possible to observe the applicability of this teaching methodology by the professors who had contact With the same during his graduations in the course of full degree in Geography of the Regional University of Cariri (URCA) where they have developed experiences with the geographic installation both within the PIBID as well as in the subject of Supervised Internship, a condition that provided knowledge of the procedural steps of the methodology, enabled them to develop it in schools of the basic education network. However, it was possible to verify some flaws regarding the stages of research, production of texts and Ideas Web, which are related to the limits imposed mainly by the issue of time and bureaucracies of the school according to the teachers, what they infer in the planning, and, however, along with its possibilities starting from a well systematized planning, adapted to the time of work of the teacher in the classroom, this methodology can contribute significantly to the teaching and learning of Geography, serving as evaluation to the process of knowledge construction by the student.